Budaya Patriarki dalam Tradisi Sasak Lombok (Analisis Wacana Kritis dalam Kumpulan Cerpen Jangan Pulang Jika Kamu Perempuan Karya Riyana Rizki) - Fatihrahma, Mahyuni; Hilmiyatun, Hilmiyatun; Amrullah, Roni (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the patriarchal culture present in Riyana Rizki's collection of short stories, Jangan Pulang Jika Kamu Perempuan, through Sara Mills' approach. The purpose of this study is to find out the patriarchal culture that occurs in the merariq tradition in the tradition of the Lombok Sasak community. This study uses a descriptive qualitative method with a data blunt technique based on the results of readers' understanding of the collection of short stories and conducting interviews with the author and several readers. Data analysis was carried out by classifying data from short story excerpts based on the theme raised, and then analyzed using Sara Mills' theory, namely the position of subject-objects and the position of the reader. The results of the study show that the merariq tradition in the Sasak Lombok community, which is depicted in the short story "Jangan Pulang Jika Kamu Perempuan," represents the strong patriarchal culture that is still inherent in social life. In this short story, men and customs are portrayed as the dominant subjects who have full authority in determining women's way of life. On the contrary, women are placed in the position of objects who must submit and accept the consequences of decisions made by men and society. Based on Sara Mills' critical discourse theory, it was found that this short story not only positions women as objects who are always blamed but also puts readers in a critical position to review the legitimacy of gender-biased customs. Readers are directed to empathize with the suffering of female figures while being invited to reject the truth claims built by the dominant voices of the culture. Thus, the short story "Jangan Pulang Jika Kamu Perempuan" can be said to be a counter-discourse that not only records reality but also offers a sharp social critique of patriarchal culture and opens up a new space of awareness about the importance of gender equality.